MATHEMATICAL METHODS FOR IMAGE PROCESSING AND MATHEMATICAL MODELING - Ždímalová, Mária; Vrábel, Marián; Boratková, Kristína; BPB MED S.R.O. (Matematichki Bilten, 2024)
This contributions deals with applied mathematical models and its application into image processing. We focus on discrete segmentation mathematical algorithms and its application in the binary segmentation of images. We improve, implement and create new own software's tools for image analyses specially graph cut and grab cut method. We optimize these algorithms and bring concrete examples in real life, biology, medicine and civil engineering.